The cGAS-STING pathway and female reproductive system diseases - Li, Ruijie; Liu, Hengwei; Liu, Yi (Frontiers in Immunology, 2024)
The cGAS-STING pathway has become a crucial role in the detection of cytosolic DNA and the initiation of immune responses. The cGAS-STING pathway not only mediates protective immune defense against various DNA-containing pathogens but also detects tumor-derived DNA to generate intrinsic anti-tumor immunity. However, abnormal activation of the cGAS-STING pathway by self-DNA can also lead to autoimmune diseases and inflammatory disorders. This article reviews the mechanisms and functions of the cGAS-STING pathway, as well as the latest research progress in female reproductive-related diseases. We focus on the regulatory mechanisms and roles of this pathway in common female reproductive disorders, discuss the clinical potential of the cGAS-STING pathway as biomarkers and therapeutic agents for female reproductive diseases, as well as the research controversies, technical issues, and biological knowledge gaps that need to be resolved. Furthermore, we provide new ideas for the treatment and prevention of these diseases.